A king lost and found: Revisiting the popular and the tribal myths of Mahabali from Kerala. Issue 1 (1st April 2016) - Kalidasan, Vinod Kottayil
This article attempts to revisit the popular as well as tribal myths of Mahabali, the former of which informs Onam – Kerala's national festival. The popular myth while mourning the loss of Mavelinadu – a utopian welfare state – also attempts to recreate the same by way of thoroughly modern political praxis. The mostly unknown tribal myths of Mahabali, from the Wayanad district, however, propose an alternative concept Mavelimantam that, while being an antithesis to the former, imagines a radical, pro-Adivasi and anti-majoritarian space. Onam symbolizes the 'return' of Mahabali who, in the popular myth, was pushed to the netherworld by an invading Deva disguised as a dwarf Brahmin. His return from 'exile' also represents a politico-economic reality of his 'former subjects' returning from their exiles abroad, especially from the Persian Gulf. While Mahabali can stage an annual return to Kerala, Maveli, the tribal chieftain whose land was usurped by the feudal lords in the tribal myths, cannot. This article also investigates notions such as body, alienation of tribal land in contemporary Kerala, politics of myths and their ramifications on modern economic, political, philosophical and cultural affairs of the state and its deeply multicultural spaces.